Synthesis and Characterization ofBiologically Active Organotin-Platinum-Imine and Organotin-Platinum-Amine Complexes - M. Al-Najjar, Ibrahim; S. Al-Diab, Salem (Asian Journal of Chemistry, 2010)
1H, 13C and 31P-chemical shifts are reported for the first time for new biologically active organotin-imine, organotin-amine ligand. and their complexes with platinum(II), complexes of the type trans-[PtCl2(PPh3)(imine)] and trans[ PtCl2(PPh3(amine)], the imine ligand being derived from 3-[tri-n-butylstannyl)benzaldehyde and primary amines; the amine ligand obtained by the reduction of the appropriate imine. The use of multinuclear spectroscopy provides strong evidence for structure determination of these complexes. Of interest is that both 1H and 13C resonances of CH=N and 13C of R-carbon data (γ-protons and β-carbons to the platinum atom), exhibit large downfield shifts upon coordination of imine (or amine) with respect to free imine (or amine). In addition, 1H, 13C and 31P-NMR spectra show that only a single rotamer exists.